First Record of the genus Lagynodes Förster, 1840 (Megaspilidae: Lagynodinae) from India, with the description of a new species and a molecular analysis - Ghosh, Amit Kumar; Kumar, Vikas; Salden, Tobias; Tyagi, Kaomud (Zootaxa, 2025)
The subfamily Lagynodinae and genus Lagynodes Förster, 1840 (Hymenoptera: Ceraphronoidea: Megaspilidae) are reported for the first time from India. Lagynodes mikoi sp. nov. is described and illustrated from West Bengal, India. The species concept is based on an integrative taxonomic approach combining morphological and molecular characters. Comparison of the COI barcode further allows clear species delimitation from other published COI sequences of Lagynodes species.